A failure-envelope-based method for the probabilistic failure prediction of composite multi-bolt double-lap joints. (1st September 2019) - Liu, Fengrui; Fang, Ziang; Zhao, Libin; Zhang, Jianyu; Hu, Ning
Abstract: A prediction method is proposed for the probabilistic failure of composite multi-bolt double-lap joints based on a single-parameter spring-based method, a failure envelope method and Monte Carlo simulation. In this method, the effects of the randomness of the laminate bearing and open-hole strength, laminate's properties, geometric parameters, clearances, tightening torques and bolt bearing chord stiffness are considered. And the application of failure envelope method leads to an advantage of a very small amount of calculation. To validate the proposed method, composite two-bolt and three-bolt double-lap joints were designed and tested to determine the stochastic failure load. Following the testing of all the necessary parameters, satisfactory agreement between the numerical and experimental stochastic failure loads of the multi-bolt joints was found. Furthermore, the sensitivities of the probabilistic failure load of multi-bolt joints were investigated. It follows that the randomness of the laminate open-hole tensile and bearing strengths have the most significant influences on the failure load, while the influences of the randomness of the other parameters are slight, which affect bolt load distribution directly, and indirectly affect the failure load through influencing the bolt load distribution.